2006
DOI: 10.1016/j.cma.2005.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Immersed finite element method and its applications to biological systems

Abstract: This paper summarizes the newly developed immersed finite element method (IFEM) and its applications to the modeling of biological systems. This work was inspired by the pioneering work of Professor T.J.R. Hughes in solving fluid-structure interaction problems. In IFEM, a Lagrangian solid mesh moves on top of a background Eulerian fluid mesh which spans the entire computational domain. Hence, mesh generation is greatly simplified. Moreover, both fluid and solid domains are modeled with the finite element metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
191
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(191 citation statements)
references
References 52 publications
(82 reference statements)
0
191
0
Order By: Relevance
“…The three values { A=1,2,3 } are the so-called principal stretches and I denotes the identity tensor. The strain invariants of Equation (25) can be expressed as functions of 2 A as…”
Section: Large Strain Hyperelasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…The three values { A=1,2,3 } are the so-called principal stretches and I denotes the identity tensor. The strain invariants of Equation (25) can be expressed as functions of 2 A as…”
Section: Large Strain Hyperelasticitymentioning
confidence: 99%
“…Within the biomedical field, for example, the interaction of a viscous incompressible fluid, such as blood with a deformable membrane, as found within heart valves, arteries or veins represents an extraordinary challenge. Research within the biomedical field could influence many aspects of diagnosis and treatment as well as the design and implementation of components such as artificial heart valves, stents and many others [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The IMFEM [78][79][80][81][82][83] is a computational framework to concurrently deal with the relevant physical interactions in biological environments [80,84,85], including fluid-structure interaction (FSI) [82,86,87], cell-cell interaction [81,88,89], thermal fluctuation [78,79,90], electrokinetics [83,91,92], self-assembly behaviour [79,[93][94][95] and other mesoscale and molecular effects [96]. In this work, the IMFEM will be used to simulate the blood flow as well as the microcirculation of NPs.…”
Section: Model and Methodologymentioning
confidence: 99%
“…Some examples for this type of approach are the boundary element method [23,26,34], the immersed boundary method [2,7,24,31], the lattice Boltzmann method [6,29] and the moving particle semi-implicit (MPS) method [19,30]). Recent reviews on these numerical methods can be found in Liu et al [18], Yamaguchi et al [33] and Lima et al [14]. Although the multiphase flow approach is a very promising method it requires massive computational power.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%